2005
DOI: 10.1007/s00259-004-1733-4
|View full text |Cite
|
Sign up to set email alerts
|

Early-stage [123I]β-CIT SPECT and long-term clinical follow-up in patients with an initial diagnosis of Parkinson’s disease

Abstract: [(123)I]beta-CIT SPECT scanning in early-stage, untreated parkinsonian patients revealed a relative sparing of the caudate nucleus in patients with IPD as compared to patients later (re)diagnosed with APS. Nevertheless, the pattern of striatal involvement appears to have little predictive value for a later re-diagnosis of APS in individual cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 35 publications
2
16
1
1
Order By: Relevance
“…In this context, Knudsen et al observed that an asymmetry index of striatal DAT binding greater than 15% allowed discrimination between early-tomoderate PD and MSA, with a sensitivity of 86% (34). However, these results were obtained in a small sample and are contradictory to other findings (9,12,31), including our own results, which do not reveal significant asymmetry indices in drug-treated PD patients.…”
Section: Presynaptic Nigrostriatal Systemcontrasting
confidence: 95%
See 1 more Smart Citation
“…In this context, Knudsen et al observed that an asymmetry index of striatal DAT binding greater than 15% allowed discrimination between early-tomoderate PD and MSA, with a sensitivity of 86% (34). However, these results were obtained in a small sample and are contradictory to other findings (9,12,31), including our own results, which do not reveal significant asymmetry indices in drug-treated PD patients.…”
Section: Presynaptic Nigrostriatal Systemcontrasting
confidence: 95%
“…In summary, the present results on the stand-alone analyses of FP-CIT SPECT, IBZM SPECT, and MIBG scintigraphy concur with previous studies reporting presynaptic nerve terminal affection, striatal D 2 receptor involvement, and myocardial sympathetic dysfunction in both PD and APD patients (9,10,12,14,31,34,41). Specifically, the present data reproduce the lower cardiac MIBG uptake in PD (vs. APD).…”
Section: Multimodal Investigationssupporting
confidence: 92%
“…We expect that the PDRP will be especially informative, because in contrast to olfaction,31 the PDRP is a progression marker 11. Moreover, PDRP expression is useful in the differential diagnosis of parkinsonian disorders,32 whereas DAT imaging is not 33…”
Section: Discussionmentioning
confidence: 99%
“…Notably, reduced binding was observed not only in the striatum, and especially the putamen, corresponding to the symptomatic limbs but also already in the contralateral putamen associated with the clinically still yet asymptomatic side of the body (23)(24)(25). The reported binding values were significantly lowered compared with those of age-matched healthy controls and showed no or almost no overlap between patients and controls.…”
Section: Early Diagnosis Of Neurodegenerative Psmentioning
confidence: 92%
“…Furthermore, longitudinal imaging studies have proven capable of determining intraindividual disease progression (24,38). Concordantly, in those studies the annual rate of decline of DAT binding ranged from 6% to 8%.…”
Section: Assessment Of Disease Progressionmentioning
confidence: 93%